Faktor-Faktor Yang Mempengaruhi Gizi Buruk Pada Balita Di Puskesmas Teling Atas Manado - Belina Lang (Student Research Journal, 2023)
Malnutrition is a phenomenon which is closely related to nutritional problems experienced by the toddler age group. Malnutrition can occur due to internal and external factors that are not prevented as early as possible and have an impact on health conditions, growth and development of toddlers, and productivity in adulthood. This phenomenon reveals the importance of preventive efforts to prevent the risk of malnutrition in children under five from all possible risk factors. This article aims to review and analyze efforts to prevent the risk of malnutrition in children under five through the literature review method. There are 10 main articles used and have been selected according to inclusion and exclusion criteria and selected through search results on Google Scholar and SINTA databases. The results of the study found that efforts to prevent malnutrition in toddlers can be carried out through various methods with the concept of education and health promotion accompanied by intervention programs, and measuring aspects of knowledge, attitudes and behavior of mothers, health workers, posyandu cadres as well as measuring weight and height. to toddlers. The optimization of health promotion programs and nutrition interventiointerventions is expected to be balanced with strengthening resources, monitoring and evaluation and close cross-sectoral coordination.